α-MSH-catabolic enzyme prolylcarboxypeptidase in nucleus accumbens shell ameliorates stress susceptibility in mice through regulating synaptic plasticity - Deng Qiao; Zhang Shao-qi; Yang Ping-fen; Dong Wan-ting; Wang Fang; Long Li-hong; Chen Jian-guo (Acta Pharmacologica Sinica; Vol 44, No 8 (August 2023): Acta Pharmacologica Sinica, 2023)
Emerging evidence demonstrates the vital role of synaptic transmission and structural remodeling in major depressive disorder. Activation of melanocortin receptors facilitates stress-induced emotional behavior. Prolylcarboxypeptidase (PRCP) is a serine protease, which splits the C-terminal amino acid of α-MSH and inactivates it. In this study, we asked whether PRCP, the endogenous enzyme of melanocortin system, might play a role in stress susceptibility via regulating synaptic adaptations. Mice were subjected to chronic social defeat stress (CSDS) or subthreshold social defeat stress (SSDS). Depressive-like behavior was assessed in SIT, SPT, TST and FST. Based on to behavioral assessments, mice were divided into the susceptible (SUS) and resilient (RES) groups. After social defeat stress, drug infusion or viral expression and behavioral tests, morphological and electrophysiological analysis were conducted in PFX-fixed and fresh brain slices containing the nucleus accumbens shell (NAcsh). We showed that PRCP was downregulated in NAcsh of susceptible mice. Administration of fluoxetine (20 mg·kg−1·d−1, i.p., for 2 weeks) ameliorated the depressive-like behavior, and restored the expression levels of PRCP in NAcsh of susceptible mice. Pharmacological or genetic inhibition of PRCP in NAcsh by microinjection of N-benzyloxycarbonyl-L-prolyl-L-prolinal (ZPP) or LV-shPRCP enhanced the excitatory synaptic transmission in NAcsh, facilitating stress susceptibility via central melanocortin receptors. On the contrary, overexpression of PRCP in NAcsh by microinjection of AAV-PRCP alleviated the depressive-like behavior and reversed the enhanced excitatory synaptic transmission, abnormal dendritogenesis and spinogenesis in NAcsh induced by chronic stress. Furthermore, chronic stress increased the level of CaMKIIα, a kinase closely related to synaptic plasticity, in NAcsh. The elevated level of CaMKIIα was reversed by overexpression of PRCP in NAcsh. Pharmacological inhibition of CaMKIIα in NAcsh alleviated stress susceptibility induced by PRCP knockdown. This study has revealed the essential role of PRCP in relieving stress susceptibility through melanocortin signaling-mediated synaptic plasticity in NAcsh.